Peningkatan Kemampuan Mengidentifikasi Unsur Intrinsik Novel Remaja Asli atau Terjemahan Dengan Mengimplementasikan Model Pembelajaran Inkuiri Pada Siswa Kelas VIII Semester Genap Tahun Pelajaran 2015/2016 di Smp Negeri 25 Bandarlampung - Akhmad Baidowi (Kantor Bahasa Lampung, 2018)
This research is motivated by the difficulty of students identifying the intrinsic elements of teen novels. The reason is that the learning model presented by the teacher is less interactive. Teaching and learning activities are still dominated by teachers. In general, the formulation of the problem of this research is How to improve the ability to identify the intrinsic elements of the original teen novel or translation by implementing the inquiry learning model in the eighth grade students of the even semester of the 2015/2016 school year in Bandarlampung State Middle School. The method used in this study is classroom action research. The purpose of this study was to describe an increase in the ability to identify the intrinsic elements of the original adolescent novel or translation with the inquiry learning model in class VIII students of State Junior High School 25 Bandar Lampung in the 2015/2016 school year. The implementation of the inquiry learning model was able to improve the ability to identify the intrinsic elements of the original teen novel or translation. The results of the study as many as 3 cycles showed an increase in learning outcomes. The first cycle learning outcomes with learning materials identified the teenage novel characters, 76% class absorption, students finished 78.9% KKM, and KKM 21% students did not complete. The learning outcomes of the second cycle of learning material explained the theme and background of the adolescent novel, the absorption of students rose to 79%, students who had completed KKM rose to 84%, while those who did not complete learning dropped to 16%. After going through repairs together with the collaborator, the learning outcomes of the third cycle of the learning material described the novel's teenage plot succeeded in increasing the absorption of students to 85%, students completing learning to 96%, and students who had not completed learning dropped to 5%. These results are in accordance with the research target, namely 95% of students complete the KKM and 85% class absorption.Based on the data from the actions taken, it can be concluded that the application of the inquiry learning model was able to improve the ability to identify the intrinsic elements of teen novels in class VIII of State Junior High School 25 Bandar Lampung 2015/2106. AbstrakPenelitian ini dilatarbelakangi adanya kesulitan siswa mengidentifikasi unsur instrinsik novel remaja. Penyebabnya adalah model pembelajaran yang disajikan oleh guru kurang interaktif. Kegiatan belajar mengajar masih didominasi oleh guru. Secara umum rumusan masalah penelitian ini adalah Bagaimana meningkatkan kemampuan mengidentifikasikan unsur intrinsik novel remaja asli atau terjemahan dengan mengimplementasikan model pembelajaran inkuiri pada siswa kelas VIII semester genap tahun pelajaran 2015/2016 di SMP Negeri 25 Bandarlampung. Metode yang digunakan dalam penelitian ini adalah penelitian tindakan kelas. Tujuan penelitian ini adalah untuk mendeskripsikan peningkatan kemampuan mengidentifikasikan unsur intrinsik novel remaja asli atau terjemahan dengan model pembelajaran inkuiri pada siswa kelas VIII SMP Negeri 25 Bandarlampung tahun pelajaran 2015/2016. Implementasi model pembelajaran inkuiri ternyata mampu meningkatkan kemampuan mengidentifikasikan unsur intrinsik novel remaja asli atau terjemahan. Hasil penelitian sebanyak 3 siklus menunjukkan adanya peningkatan hasil belajar. Hasil pembelajaran siklus satu dengan materi pembelajaran mengidentifikasi karakter tokoh novel remaja, daya serap kelas 76%, siswa tuntas KKM 78,9 %, dan siswa belum tuntas KKM 21%. Hasil pembelajaran siklus dua materi pembelajaran menjelaskan tema dan latar novel remaja, daya serap siswa naik menjadi 79%, siswa yang sudah tuntas KKM naik menjadi 84%, sedangkan yang belum tuntas belajar turun menjadi 16%. Setelah melalui perbaikan bersama kolabolator, hasil pembelajaran siklus ketiga materi pembelajaran mendeskripsikan alur novel remaja berhasil meningkatkan daya serap siswa menjadi 85%, siswa tuntas belajar menjadi 96 %, dan siswa yang belum tuntas belajar turun menjadi 5%. Hasil ini sudah sesuai dengan target penelitian yaitu 95 % siswa tuntas KKM dan daya serap kelas 85%. Berdasarkan data hasil tindakan yang dilakukan, dapat disimpulkan bahwa implementasi model pembelajaran inkuiri mampu meningkatkan kemampuan mengidentifikasi unsur intrinsik novel remaja pada siswa kelas VIII SMP Negeri 25 Bandarlampung tahun pelajaran 2015/2106.